2015
DOI: 10.1002/etc.3137
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration and depuration of 14C‐labeled 17α‐ethinyl estradiol and 4‐nonylphenol in individual organs of the marine bivalve Mytilus edulis L.

Abstract: Endocrine-disrupting compounds (EDCs), including 17α-ethinyl estradiol (EE2) and 4-nonylphenol (4-NP), enter coastal environments primarily in effluents of wastewater treatment facilities and have become ubiquitous in marine surface waters, sediments, and biota. Although EE2 and 4-NP have been detected in marine shellfish, the kinetics of bioconcentration and their tissue distribution have not been thoroughly investigated. The authors performed bioconcentration and depuration experiments in the blue mussel, My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…The observed K d values of E1, E2, and EE2 were similar to previous reports for activated sludge (Andersen et al 2005;Clara et al 2004). In general, the change in aqueous-phase concentration between dosing events can be attributed to abiotic transformation (Liu and Liu 2004;Silva et al 2012), metabolism (Ivanov et al 2010;Welshons et al 2003), sorption to sediment (Andersen et al 2005), and accumulation in biota (Dussault et al 2009a;Ricciardi et al 2016). Because the aqueous-and fecal matter-phase concentrations followed the same trends, some combination of the above processes likely manifested; however, the degradation pathways were not specifically elucidated in this work.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The observed K d values of E1, E2, and EE2 were similar to previous reports for activated sludge (Andersen et al 2005;Clara et al 2004). In general, the change in aqueous-phase concentration between dosing events can be attributed to abiotic transformation (Liu and Liu 2004;Silva et al 2012), metabolism (Ivanov et al 2010;Welshons et al 2003), sorption to sediment (Andersen et al 2005), and accumulation in biota (Dussault et al 2009a;Ricciardi et al 2016). Because the aqueous-and fecal matter-phase concentrations followed the same trends, some combination of the above processes likely manifested; however, the degradation pathways were not specifically elucidated in this work.…”
Section: Resultssupporting
confidence: 88%
“…(2). Although bioaccumulation of E1 (Gomes et al 2004;Lai et al 2002) andEE2 (Al-Ansari et al 2013;Dussault et al 2009a;Ricciardi et al 2016) has been observed in previous laboratory exposure experiments, the reported BAFs vary over a wide range for different organisms. Lai et al (2002) reported a BAF of 27 L kg −1 for E1 in a green microalgae (Chlorella vulgaris) over 48 h with an aqueous-phase concentration around 2 μg L −1 .…”
Section: Bioaccumulation Of Estrogens and Uv-filters In Crayfish Tail Tissuementioning
confidence: 93%
See 2 more Smart Citations
“…Research focus previously has been on freshwater systems, and marine ecosystems have been identified here as being underrepresented and requiring further investigation . This is particularly important in coastal environments, where human impacts are pronounced and dynamic, in terms of daily physicochemical cycles; the use of innovative methods for examining bioavailability and potential risks to marine organisms is therefore highly desirable . In addition, the terrestrial environment increasingly is receiving attention, especially with respect to crop exposure through wastewater and biosolids application.…”
Section: The Second Special Issue—where We Have Come From and Where mentioning
confidence: 99%